2019
DOI: 10.1057/s41599-019-0254-5
|View full text |Cite
|
Sign up to set email alerts
|

Making the smart meter social promotes long-term energy conservation

Abstract: Managing demand for energy is becoming increasingly important for efforts to shift toward more sustainable lifestyles. Managing demand for energy involves changes in human behaviour, and can be achieved through more efficient uses of technology, and through conservation. Feedback is often cited as a critical tool to promote energy conservation and efficiency, but recent studies in behavioural science suggest that feedback alone may not be enough to promote lasting changes in behaviour. As an alternative, recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 45 publications
2
41
0
Order By: Relevance
“…For example, Graffeo et al [38] found that Israeli households who were provided with an in-group normative feedback message (from the same neighborhood) decreased their energy consumption more so than those who received an out-group normative feedback message (from another city). As we attempt to promote the large-scale uptake of a smart energy device, this study refers to a broader in-group norm (i.e., households in the US) as an effective referent group [10].…”
Section: Using Descriptive Norms To Promote Smart Energy Devicesmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, Graffeo et al [38] found that Israeli households who were provided with an in-group normative feedback message (from the same neighborhood) decreased their energy consumption more so than those who received an out-group normative feedback message (from another city). As we attempt to promote the large-scale uptake of a smart energy device, this study refers to a broader in-group norm (i.e., households in the US) as an effective referent group [10].…”
Section: Using Descriptive Norms To Promote Smart Energy Devicesmentioning
confidence: 99%
“…Such a smart energy device allows individuals to reduce their energy use and eventually begin practicing more energy conservation behaviors (e.g., reducing the temperature and amount of heat consumed, using fewer household appliances). Indeed, previous literature has shown that providing households with a smart energy device can lead to a decrease in energy consumption [9,10]. Notably, some authors have suggested that using such devices merely result in short-term energy reductions [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations